Analisis Konsep Riba dalam Pandangan Fuqaha: Perspektif Filsafat Hukum Ekonomi Syariah - Ratnasari, Ai Reni; Nurrohman; Lena Ishelmiany Ziaharah; Adang Sonjaya; Desi Cahya Anggraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the economic impact of usury (riba) on Islamic economics and the challenges faced in applying Islamic economic principles in the context of economic globalization. Riba, which is strictly prohibited in Islamic law, is seen as a source of economic injustice that exacerbates social and economic inequalities. The research analyzes how the principles of social justice and balance, which are the foundation of Islamic economics, can offer solutions to the inequality issues caused by the interest-based system. Through a literature analysis and case study approach, it was found that while the application of Islamic economics faces significant challenges in the context of the global capitalist system, the principles embedded in Islamic finance, such as justice, balance, and social sustainability, can provide a more stable and ethical alternative. The findings of this study suggest that Islamic economics has the potential to offer solutions to global economic instability and contribute to more equitable economic sustainability. This research also provides suggestions for future studies on the implementation of Islamic economics in a financial world increasingly influenced by digitalization and financial technologies.